Integrative single-cell RNA-seq and spatial transcriptomics analyses reveal diverse apoptosis-related gene expression profiles in EGFR-mutated lung cancer - Izumi, Motohiro; Fujii, Masanori; Kobayashi, Ikei S.; Ho, Vivian; Kashima, Yukie; Udagawa, Hibiki; Costa, Daniel B.; Kobayashi, Susumu S. (Cell death & disease, 2024)
In EGFR -mutated lung cancer, the duration of response to tyrosine kinase inhibitors (TKIs) is limited by the development of acquired drug resistance. Despite the crucial role played by apoptosis-related genes in tumor cell survival, how their expression changes as resistance to EGFR-TKIs emerges remains unclear. Here, we conduct a comprehensive analysis of apoptosis-related genes, including BCL-2 and IAP family members, using single-cell RNA sequence ( scRNA-seq) and spatial transcriptomics (ST). scRNA-seq of EGFR -mutated lung cancer cell lines captures changes in apoptosis-related gene expression following EGFR-TKI treatment, most notably BCL2L1 upregulation. scRNA-seq of EGFR -mutated lung cancer patient samples also reveals high BCL2L1 expression, specifically in tumor cells, while MCL1 expression is lower in tumors compared to non-tumor cells. ST analysis of specimens from transgenic mice with EGFR-driven lung cancer indicates spatial heterogeneity of tumors and corroborates scRNA-seq findings. Genetic ablation and pharmacological inhibition of BCL2L1 /BCL-XL overcome or delay EGFR-TKI resistance. Overall, our findings indicate that BCL2L1 /BCL-XL expression is important for tumor cell survival as EGFR-TKI resistance emerges.